Sukses Impementasi ASI Eksklusif Pada Ibu Bekerja - Wandi, Wandi (Malang Journal of Midwifery (MAJORY), 2019)
The success of implementing Exclusive Breastfeeding on working mothers is a very rewarding experience. The purpose of this study is to describe the experience of exclusive breastfeeding on working mothers. The type of this research is a qualitative study of phenomenology on 7 informants. The data was collected using in-depth interview. The results of the study found: (a) Exclusive breastfeeding processes for working mothers may be provided directly and indirectly, (b) factors affecting exclusive breastfeeding are support from health, family and co-workers teams, (c) exclusion of breastfeeding difficulties including reduced milk production, Nipple blisters, swollen breasts and limited facilities. Keywords: Exclusive Breastfeeding, Experience, Working Mother